Across-shift changes in the pulmonary function of meat-wrappers and other workers in the retail food industry. - Eisen, Ellen A.; Wegman, David H.; Smith, Thomas J. (Scandinavian Journal of Work, Environment & Health, 1985)
Pulmonary function was measured before, during, and after the end of the workshift in 83 workers in the retail food industry. All acute changes in forced expiratory volume in 1 s were standardized for lung size before the magnitude of the changes were compared between the workers exposed and unexposed to the use of hot wires for cutting plastic film. No association was found between acute drop in pulmonary function and either direct or indirect exposure in the absence of a history of asthma or allergy to inhaled materials. The borderline significance of an interaction term between exposure and asthma/allergy in a regression analysis suggests that workers with a history of asthma or atopy may have an acute response to hot-wire wrapping emissions.